Therapeutic phlebotomy - Angulo, Ivan L.; Papa, Fábio V.; Cardoso, Fernanda G. (Medicina (Ribeirao Preto), 1999)
Therapeutic phlebotomy is an old and simple way to relieve sintoms but can raize life spectancy and bring better quality of life. It is incrisingly indicated nowadays, alone or in combination with others therapeutic tools. It can be used to control high blood viscosity in polycythemias or washout of toxic metabolic products or iron in parenquimal cells. At Hemocentro, in Ribeirão Preto, polycythemias were the most common indication for bloodletting, 42% after kidney transplants, 30% by lung and heart diseases, and 15% by polycythemia vera. Toxic metabolic products motivated bloodletting in 9% by iron overload and 4% by porphyria. No adverse efects were noted, target hematocrits were considered adequate in polycythemias and periodic bloodletting exerced an effective control of symptoms. Sugestions were made for better medical practices.